CHALLENGES OF STAY-AT-HOME POLICY IMPLEMENTATION DURING THE CORONAVIRUS (COVID-19) PANDEMIC IN INDONESIA - Febri Endra Budi Setyawan; Retno Lestari (Indonesian Journal of Health Administration (Jurnal Administrasi Kesehatan Indonesia), 2020)
The coronavirus disease 2019 (COVID-19) has been labelled as a global pandemic disease by the World Health Organization. The number of infections in Indonesia rose significantly to 8211 cases, and 689 coronavirus deaths were reported on April 24th, 2020. We knew that the Indonesian Government has made numerous strategies to control the spread of infection in our community, but implementation plans were limited in addressing the challenges of stay-at-home policy. These challenges may include economic impact due to COVID-19, struggles for work-from-home, and leaders' ability to influence the society.